Communication Climate and Work Engagement: The Relevance of Trust and Openess - Sampayo, M.M.; Silva, S.A. (16th European Congress of Work and Organizational Psychology, 2013)
The communication climate is critical to motivate employees to achieve organizational goals, for instance will strengthen the organizational identification associated with more job satisfaction, more involvement in the work, lower intent to leave work (e.g. Smidt et al, 2001).Bakker & Leiter (2010) emphasize that employees' responses to policies, practices and organizational structures affect their potential to experience engagement. However until now it was not explored the role of a communication climate in work engagement.We hypothesized that a more positive communication climate (trust and openness in communication; supportiveness; participation in decision-making) would be related to higher work engagement (vigor, dedication and absorption). Expecting also a more strong effect of a communication characterized by trust and openness.